Visible-light-enhanced power generation in microbial fuel cells coupling with 3D nitrogen-doped graphene. Issue 72 (16th August 2017) - Guo, Dan; Song, Rong-Bin; Shao, Hao-Hua; Zhang, Jian-Rong; Zhu, Jun-Jie
Abstract : A high performance visible-light-assisted MFC was successfully fabricated based on the synergistic effect between a novel 3D NG-SS anode and a visible-light responsive CuS photocathode. Abstract : A new visible-light-assisted microbial fuel cell composed of a three-dimensional nitrogen-doped graphene self-standing sponge anode and a photoresponsive cathode has been developed for achieving multiple energy conversion and a higher power output.